(untitled) (Research, Society and Development, 2021)
One of the challenges in pharmaceutical logistics is to ensure that thermolabile drugs reach the patient with quality. This prospective cross-sectional study aimed to analyze the current cold chain scenario in Brazil. A semi-structured electronic questionnaire was applied for data collection. The total sample was 1793 pharmacists (CI: 99.998%; ME: 5%; p: 0.00002). 74.1% of the pharmacists reported that transportation is the most critical stage; 97.2% stated that the chosen mode influences the quality of the products; 52.5% reported only having partial parameters (tools) for the assessment of quality and that thermolabile medications possibly arrive altered to the final consumer due to the cold chain (59.8%); 66.9% do not have specific training on thermolabile medicines and 50.9% did not receive the technical data sheets of the products through the registration holders; 20.7% reported not being able to analyze or perform any activity related to qualification and validation. The absence of markings in the manual records (50.6%), the non-validation of the equipment used for conservation (30.6%) and the incorrect storage of medicines at domestic refrigerators (45.5%), near food (35.8%), were also noted. The non-measurement of the temperature of the products received was affirmed by 56.7%, as well as the use of thermometers to measure parameters (45.3%); 58.7% of the establishments do not have thermal mapping and 55.3% of the professionals are unaware of the thermal durability of the packaging. Due potentially inadequate situation, there is urgency to implement tools that guarantee the quality of thermolabile drugs in all its logistical stages.